Influence of rhizosphere priming effects on accumulation and decomposition of soil organic carbon - MO Chaoyang; ZHANG Xinlin; YANG Jingping (浙江大学学报. 农业与生命科学版, 2021)
By using a 13C natural abundance method, this study investigated the rhizosphere priming effects (RPE) of sorghum and maize growing in two types of soil (paddy soil and lou soil) at two stages, and the contents of light fraction organic carbon (ρ1＜1.7 g/cm3) and heavy fraction organic carbon (ρ2＞1.7 g/cm3) of soil were also determined. The results showed that planting crops significantly enhanced the soil organic matter decomposition. And the maize induced the most CO2-C flux derived from soil organic carbon at the trumpet stage in paddy soil, which reaching 18.49 mg/(kg•d). The maize induced stronger RPE than sorghum across all growth stages, which indicated that planting maize would bring more CO2 emission. The content of light fraction organic carbon of soil changed significantly, while the content of heavy fraction organic carbon remained stable during RPE process. Hence, RPE may directly function on the light fraction organic carbon. This study provides the theoretical basis for controlling the RPE intensity reasonably and reducing global CO2 fluxes.